Experimental Evidence of an Optical Bistability Based on Self - Focusing - Hussain A. Badran (University of Thi-Qar Journal of Science, 2019)
Optical bistability based on Self – Focusing of low power CW He-Ne laser radiation ,at the wavelengthof 0.632m ,has been experimentally evidence in liquid CSusing a new simple and effective technique.New experimental results supporting the hypothesis that optical bistability based on self –focusing of laserradiation occurs in liquid are present in this article. Mirrorless limiting mode is observed too.